2015
DOI: 10.1590/1678-4499.0265
|View full text |Cite
|
Sign up to set email alerts
|

Classification of physiological races of Fusarium oxysporum f. sp. phaseoli in common bean

Abstract: Fusarium wilt, caused by Fusarium oxysporum Schlecht. f. phaseoli Kendrick and Snyder (FOP), is a major disease of common bean, causing large economic losses. Genetic resistance is one of the main mechanisms of pathogen control, and knowledge of the physiological variability is fundamental in breeding for resistant cultivars. Thus, a method of pathogen classification that describes the variability and is useful in plant breeding of isolates from different sources was evaluated by different methodologies. Commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 11 publications
0
23
0
5
Order By: Relevance
“…Fusarium species are soil-borne fungi that can cause rot of the root, stem, and fruit or vascular wilt in a wide range of crop plants, and they survive as saprophytes [24]. The wide range of different races contributes to the taxonomic complexity [25,26]. Mycotoxin production by Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Fusarium species are soil-borne fungi that can cause rot of the root, stem, and fruit or vascular wilt in a wide range of crop plants, and they survive as saprophytes [24]. The wide range of different races contributes to the taxonomic complexity [25,26]. Mycotoxin production by Fusarium spp.…”
Section: Discussionmentioning
confidence: 99%
“…According to Fourie et al [22] parasexuality arises by high mutations which may occur among the isolates. High Heterokaryosis has also been associated with continuous cultivation of the host crop [18]. The growth of the French bean in the study area is through continuous cropping.…”
Section: Discussionmentioning
confidence: 87%
“…However, in this study most isolates were highly virulent. A study by Francisco et al [18] in Brazil also demonstrated a prevalence of higher difference in pathogenic potential among 25 isolates of F. oxysporum f. sp. phaseoli.…”
Section: Discussionmentioning
confidence: 88%
“…In general, the results of studies developed by research organizations in recent decades have led to an increase in total production and a decrease in growing area, which shows an expressive increase in yield beginning in the 1984/1985 crop season. A significant part of this result is attributable to some crop management factors, but plant breeding is the largest factor responsible for integrating genetic resistance to diseases and increasing the yield capacity of cultivars (Carbonell et al 2010, Barili et al 2015, Henrique et al 2015, Azevedo et al 2015, Melo et al 2017, Pelegrini et al 2017.…”
Section: Af Chiorato Et Almentioning
confidence: 99%